Kecemasan Lanjut Usia Terhadap Kematian Di Panti Sosial Tresna Werdha Budi Mulia 1 Kelurahan Cipayung Kecamatan Cipayung Kota Jakarta Timur - Fariskha, Arry Siti; Agiati, Raden Enkeu; Indrakentjana, Bambang (Pekerjaan Sosial, 2025)
Elderly anxiety about death refers to an unpleasant condition that arises when a person thinks about cognitive, affective, physiological, and behaviorally perceived death. This study aims to obtain an empirical description of: 1) respondent characteristics, 2) cognitive anxiety, 3) affective anxiety, 4) physiological anxiety, and 5) behavioral anxiety that respondents have towards death. The method used in this study is a quantitative research method with a descriptive survey. The data sources used are primary and secondary data sources. The population in this study is 62 elderly people in the Tresna Werdha Budi Mulia 1 Social Home, Cipayung Village, Cipayung District, East Jakarta City. The sampling technique in this study is purposive sampling using an iteration technique. The data collection techniques used are questionnaires and documentation studies. The research instrument uses a rating scale. The validity tests used are face validity tests and reliability tests using Alpha Cronbach. The results showed that the anxiety of the elderly towards death was in the low category. However, cognitive, physiological, and behavioral elderly anxiety about death is relatively high.